The relation between athletes` negative performance stress and vigour: A moderated mediation analysis including rumination and psychological capital - Balk, Y. A.; Ehren, M. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Mentally disconnecting from sport is an important psychological recovery experience for athletes to cope with the demands of training and competition. Yet, those same sport-related demands can potentially interfere with athletes` ability to disconnect. Specifically, negative feedback, substandard performances, or mistakes could evoke ruminative thoughts, which likely impairs psychological recovery and might lead to impaired well-being. However, athletes` psychological capital (PsyCap) might help them to effectively deal with negative performance stress, thereby limiting its impact on rumination and subsequent well-being (i.e., vigour). The first aim of this study was to therefore investigate whether sport-related rumination mediates the relation between negative performance stress and vigour. The second aim was to examine whether athletes` psychological capital moderates the relation between 1) negative performance stress and rumination and 2) negative performance stress and vigour. A total sample of 169 amateur athletes (n = 77), semi-professional athletes (n = 42) and professional athletes (n = 50) filled in an online survey (mean age = 22.62, SD = 5.18, 50% male, 50% female). Analyses using PROCESS showed a positive relation between negative performance stress and vigour (B = -.15, SE = .06, t(166) = -2.56, p = .011, 95% CI [-.27, -.03]). Negative performance stress was positively related to rumination (B = .44, SE = .06, t(166) = 7.34, p < .001, 95% CI [.32, .56]). Furthermore, rumination was negatively related to vigour (B = -.16, SE = .08, t(166) = -2.12, p = .035, 95%CI [- .31, -.01]). Results also revealed a significant indirect effect of rumination between negative performance stress and vigour (B = -.07, 95% CI [- .150, -.002]). As the direct effect of negative performance stress on vigour became was not significant (B = -.08, p = .231, 95% CI [-.21, .05]), rumination fully mediated the relation between negative performance stress and vigour. Finally, psychological capital was negatively associated with rumination (B = -.28, SE = .13, t(166) = -2.24, p = .026, 95% CI [-.52, -.03]) and positively associated with vigour (B = .53, SE = .12, t(166) = 4.53, p < .001, 95% CI [.30, .77]). However, psychological capital did not moderate the relations between negative performance stress and rumination or vigour (p`s > .17). Thus, the mediated moderation model was not supported. Taken together, these findings show that negative performance stress experienced by athletes is negatively associated with vigour, through increased rumination about their sport. PsyCap did not attenuate these relations, although it appears to benefit athletes` general levels of rumination and well-being. Coaches and sport psychologists should be aware of how athletes cope with negative performance stress and assist them in reducing ruminative thoughts to optimize psychological recovery processes and well-being.